The development of stereoscopic warehouse stacker control system based on motion controller - Sun Xuan; Ma Zhedong; Wang Zhiyong; Ai Changsheng (MATEC Web of Conferences, 2017)
In order to meet the requirement of high efficiency, high accuracy, high reliability and high expansibility of stacker. The stacker control system based on motion controller is developed,which uses digital control technology of NC machine tools for reference and adopts the half closed loop control system of motion controller and servo drive system to realize high efficiency, high precision and high reliable motion control of stacker.Using the network interface of controller interact with the logistics system server, storage management, computer information management system of ERP, AGV car, palletizing robot and other equipment.Make it becomes the organic part of the logistics system,which provides a good solution to improve the level of enterprise logistics automation.